Expression of Fas ligand and Caspase-3 contributes to formation of immune escape in gastric cancer - Zheng, Hua-Chuan (World J Gastroenterol, 2003)
AIM: To study the role of Fas ligand (FasL) and Caspase-3 expression in carcinogenesis and progression of gastric cancer and molecular mechanisms of relevant immune escape. METHODS: FasL and Caspase-3 expression was studied in adjacent epithelial cells, cancer cells and lymphocytes of primary foci, and cancer cells of metastatic foci from 113 cases of gastric cancer by streptavidin-biotin-peroxidase (S-P) immunohistochemistry. Expression of both proteins in cancer cells of primary foci was compared with clinicopathological features of gastric cancer. The relationship between FasL expression in cancer cells and Caspase-3 expression in cancer cells or infiltrating lymphocytes of primary foci was investigated. RESULTS: Cancer cells of primary foci expressed FasL in 53.98% (61/113) of gastric cancers, more than their adjacent epithelial cells (34.51%, 39/113) (P = 0.003, χ(2) = 8.681), while the expression of Caspase-3 in cancer cells of primary foci was detected in 32.74% (37/113) of gastric cancers, less than in the adjacent epithelial cells (50.44%, 57/113) (P = 0.007, χ(2) = 7.286). Infiltrating lymphocytes of the primary foci showed positive immunoreactivity to Caspase-3 in 70.80% (80/113) of gastric cancers, more than their corresponding adjacent epithelial cells (P = 0.001, χ(2) = 10.635) or cancer cells of primary foci (P = 0.000, χ(2) = 32.767). FasL was less expressed in cancer cells of metastases (51.16%, 22/43) than in those of the corresponding primary foci (81.58%, 31/38) (P = 0.003, χ(2) = 9.907). Conversely, Caspase-3 was more expressed in cancer cells of metastases (58.14%, 25/43) than in those of the corresponding primary foci (34.21%, 13/38) (P = 0.031, χ(2) = 4.638). FasL expression was significantly correlated with tumor size (P = 0.035, rs = 0.276), invasive depth (P = 0.039, rs = 0.195), metastasis (P = 0.039, rs = 0.195), differentiation (P = 0.015, rs = 0.228) and Lauren’s classification (P = 0.038, rs = 0.196), but not with age or gender of patients, growth pattern or TNM staging of gastric cancer (P > 0.05). In contrast, Caspase-3 expression showed no correlation with any clinicopathological parameters described above in cancer cells of the primary foci (P > 0.05). Interestingly, FasL expression in primary gastric cancer cells paralleled to Caspase-3 expression in infiltrating lymphocytes of the primary foci (P = 0.016, χ(2) = 5.825). CONCLUSION: Up-regulated expression of FasL and down-regulated expression of Caspase-3 in cancer cells of primary foci play an important role in gastric carcinogenesis. As an effective marker to reveal the biological behaviors, FasL is implicated in differentiation, growth, invasion and metastasis of gastric cancer by inducing apoptosis of infiltrating lymphocytes. Chemical substances derived from the primary foci and metastatic microenvironment can inhibit the growth of metastatic cells by enhancing Caspase-3 expression and diminishing FasL expression.